The Creation of the Diocese of Bacolod in 1932 - Avellaneda, OAR, Miguel (Philippine Social Science Journal, 2020)
The creation of a mission territory evangelized for many decades or centuries by Augustinian Recollect missionaries into an apostolic vicariate or diocese was always an occasion for jubilation for them and crowing glory of their efforts. This was the case of the Diocese of Bacolod in Negros Island whose evangelization was entrusted to them in 1848. Thus the Recollect priests of the welcomed the good news and the arrival of the newly consecrated first local ordinary of Bacolod, Bishop Casimiro Lladoc, and his Manila entourage that included the Apostolic Delegate Guglielmo Piani, Bishop McCloskey of Jaro, and Father Leoncio Reta at Talisay parish church on 24 October 1933, earnestly urged parishioners to greet him along the way to the Recollect-built San Sebastian Cathedral and feted him with programs, speeches, and festive meals.